2006
DOI: 10.1007/s10886-006-9051-x
|View full text |Cite
|
Sign up to set email alerts
|

Fragrance of Canada Thistle (Cirsium arvense) Attracts Both Floral Herbivores and Pollinators

Abstract: The evolution of floral scent as a plant reproductive signal is assumed to be driven by pollinator behavior, with little attention paid to other potential selective forces such as herbivores. I tested 10 out of the 13 compounds emitted by dioecious Cirsium arvense, Canada thistle, including 2-phenylethanol, methyl salicylate, p-anisaldehyde, benzaldehyde, benzyl alcohol, phenylacetaldehyde, linalool, furanoid linalool oxides (E and Z), and dimethyl salicylate. Single compounds (and one isomer) set out in scent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
139
0
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 153 publications
(147 citation statements)
references
References 36 publications
6
139
0
2
Order By: Relevance
“…While a growing number of studies have demonstrated that floral display or reward can be costly due to the attraction of antagonists (Brody and Mitchell 1997;Adler and Bronstein 2004;Ashman et al 2004b;Strauss and Irwin 2004), the current study is one of few to address the role of scent in attracting pollinators compared to herbivores. Similar to our study, specific floral volatiles present in C. arvense scent attracted just pollinators, just herbivores, or both pollinators and herbivores (Theis 2006). In addition to having two different corolla shapes, P. viscosum has two distinct scent morphs that attract different types of pollinators depending on the presence of floral antagonists (Galen et al 1987;Galen and Cuba 2001).…”
Section: Discussionsupporting
confidence: 83%
“…While a growing number of studies have demonstrated that floral display or reward can be costly due to the attraction of antagonists (Brody and Mitchell 1997;Adler and Bronstein 2004;Ashman et al 2004b;Strauss and Irwin 2004), the current study is one of few to address the role of scent in attracting pollinators compared to herbivores. Similar to our study, specific floral volatiles present in C. arvense scent attracted just pollinators, just herbivores, or both pollinators and herbivores (Theis 2006). In addition to having two different corolla shapes, P. viscosum has two distinct scent morphs that attract different types of pollinators depending on the presence of floral antagonists (Galen et al 1987;Galen and Cuba 2001).…”
Section: Discussionsupporting
confidence: 83%
“…The production of such a diverse array of compounds is likely to incur energetic (Gershenzon 1994;Wright and Schiestl 2009) and ecological costs, because the same compounds that attract mutualistic insects also may attract antagonistic herbivores and seed predators (Irwin et al 2004;Proffit et al 2007;Schiestl et al 2011;Theis 2006;Theis and Adler 2012;Wright and Schiestl 2009).…”
Section: Introductionmentioning
confidence: 99%
“…However, plants are challenged by constantly changing abiotic and biotic environmental conditions that might affect a plant's capacity to invest in sexual reproduction (Euler and Baldwin, 1996;Carroll et al, 2001;GarcĂ­a and EhrlĂŠn, 2002). Besides direct impacts, like floral oviposition (DufaĂż and Anstett, 2003) or floral herbivory (Leege and Wolfe, 2002;RĂś se and Tumlinson, 2004;Theis, 2006;Sanchez-Lafuente, 2007), flowers are mostly exposed to a changing environment as part of an entirely affected plant (Sampson and Cane, 1999;Carroll et al, 2001). One of the most deleterious biotic influences on plants is green leaf herbivory.…”
mentioning
confidence: 99%